The “Instructional Design 101” Course: Development of a Commercial Online Course with Microlearning Approach - Shabrina, Masyitha Nur; Hardika, Hardika; Dio Lingga; Muttaqin, Nabil (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2024)
In light of the burgeoning advancement of digital technologies and the subsequent rise of online courses, this study seeks to explore the commercial potential of an online course titled "Introduction to Instructional Design." This course leverages the innovative approach of microlearning, breaking down complex concepts into manageable modules. Given the growing demand for digital learning tools, the commercial viability of such a course is becoming increasingly significant, thereby presenting a promising avenue for educators, institutions, and course developers. The study employed the ADDIE model for course creation, which entails Analysis, Design, Development, Implementation, and Evaluation. This approach ensures a comprehensive analysis of the learner's needs and course objectives. The developed course comprises a curriculum of 10 modules, each containing six submodules, alongside video and text-based learning materials. Expert review yielded a weighted mean of 3.42, denoting the course as 'effective.' The findings underline the relevance and potential profitability of such a course in the current digital learning landscape.